Estratégia educativa para a prevenção de vulvovaginites em mulheres em privação de liberdade - Lima, Fabiane da Silva Severino (2024)
Introduction: Worldwide, there is an increase in the number of women deprived of their liberty, who, in general, experience conditions where fundamental rights are fragile. The context of female incarceration can increase the spread of infections of the female reproductive tract, including vulvovaginitis, which can be prevented through effective educational actions regarding healthy intimate hygiene habits. However, there is a gap in the literature regarding educational actions aimed at this purpose in the population deprived of liberty. Objective: to evaluate the effectiveness of the health educational strategy “Xô vaginitis!” to promote knowledge, attitude and practice on healthy hygiene habits for the prevention of vulvovaginitis in women deprived of liberty. Methodology: This is an experimental study, of the Randomized Clinical Trial (RCT) type, carried out in women's penitentiary units in the State of Ceará, from September to November 2022. Two random groups were organized (CG and GI). The sample consisted of 387 women deprived of their liberty. The IG underwent participation in an educational strategy entitled “Xô Vaginitis”, while the CG remained with conventional health care. In both groups, the General Social and Health Status Assessment Questionnaire and the Knowledge, Attitudes and Practices Assessment Survey (CAP Survey) were applied regarding the adoption of intimate hygiene habits to prevent vulvovaginitis. Statistical analyzes were carried out with the aid of R software version 4.2.2 and IBM SPSS Statistics version 22. The research was submitted for consideration by the UFC Research Ethics Committee through Brazil Platform. Results: The final sample corresponded to 387 women, 208 (53.75%) belonging to the CG and 179 (46.25%) to the IG. The majority (n: 219, f: 56.6%) had a residential address in the interior of the state of Ceará, declared themselves to be mixed race (n: 303, f: 78.3%), cisgender (n: 372, f : 96.1%), heterosexual (n: 248, f: 64.1%), single (n: 257, f: 66.4%), mothers (n: 319, f: 82.9%), with a predominance of Christian religiosity (n:340, f: 87.9%). The majority owned their own home (n: 184, f: 47.5%) or rented it (n: 179, f: 46.3%). After the intervention, an increase in the CAP level of women regarding the adoption of healthy hygiene habits to prevent vulvovaginitis was identified in both groups. However, the level of knowledge and attitudes had a more significant increase in the intervention group. The report of being single was shown to be a risk factor for the development of an inadequate attitude. Women who reported “having enough running water for personal and intimate hygiene” and “having a toilet installed in the cell” were the ones who, in this study, showed an increase in the CAP level. Furthermore, the fact that the woman had participated in an educational activity on intimate hygiene had a positive association with a better level of knowledge measured. Conclusion: It is concluded that the educational strategy “Xô vaginitis” was effective in promoting knowledge, attitude and practice about healthy hygiene habits for the prevention of vulvovaginitis in women deprived of liberty.